IMMU-21. GLIOMA-DERIVED FACTORS RECRUIT AND INDUCE AN IMMUNE SUPPRESSIVE PHENOTYPE IN BONE MARROW-DERIVED CCR2+ MYELOID CELLS. (14th November 2022) - Takacs, Gregory; Kreiger, Christian; Luo, Defang; Tian, Guimei; Deleyrolle, Loic; Harrison, Jeffrey
Abstract: INTRODUCTION: Infiltrating immune-suppressive myeloid cells represent a tumor supportive population that contributes to immune checkpoint inhibitor resistance and poor survival in Glioblastoma (GBM) patients. We have previously characterized monocytic-myeloid derived suppressor cells (M-MDSCs) based on their dual expression of chemokine receptors CCR2 and CX3CR1(CCR2 + /CX3CR1 + ). Genetic and pharmacologic targeting of CCR2, in combination with PD-1 blockade, reduced the percentage of M-MDSCs in the glioma-microenvironment and slowed the progression of KR158 and 005GSC murine gliomas. Additional studies are needed to investigate the chemokines responsible for the tumor recruitment of CCR2+/CX3CR1+ cells and the impact of glioma derived factors on their immune suppressive phenotype. OBJECTIVE: Evaluate the effect of glioma derived factors on the migration and suppression of bone marrow CCR2 + /CX3CR1 + myeloid cells. METHODS: A transwell migration assay was utilized to determine the migratory ability of CCR2 + /CX3CR1 + cells to KR158B conditioned in the presence of CCL2 and CCL7 neutralizing antibodies. Ly6G-/GR1 + cells were isolated from bone marrow cultured with KR158B conditioned media and co-cultured with freshly isolated T-cells to examine their immune-suppressive phenotype. RESULTS: KR158B gliomas differentially upregulate cytokines including CCL2, IL6, G-CSF, GM-CSF as compared to healthy naive brains. KR158B conditioned media increased the percentage of bone marrow-derived CCR2 + /CX3CR1 + cells that are CD11b +, Ly6C hi, and Ly6G - . Bone marrow-derived CCR2+/CX3CR1+ cells expanded in KR158B condition media suppress both CD4+ and CD8+ T cell proliferation. Bone marrow-derived CCR2+/CX3CR1+ cells migrate to recombinant CCL2 and CCL7 as well as KR158B glioma conditioned media. Migration to conditioned media is completely inhibited by the combination of CCL2 and CCL7 neutralizing antibodies. High CCL2 and CCL7 are associated with poor prognosis in human GBM. CONCLUSION: Glioma-derived CCL2 and CCL7 mediate migration of CCR2+ myeloid cells into the tumor microenvironment in a redundant manner. Additional glioma-derived factors induce CCR2+/CX3CR1+ myeloid cells to a CD4/8+ T cell suppressive state.